Relationships of brain white matter microstructure with clinical and MR measures in relapsing-remitting multiple sclerosis. - Giorgio, A; Palace, J; Johansen-Berg, H; Smith, S; Ropele, S; Fuchs, S; Wallner-Blazek, M; Enzinger, C; Fazekas, F (2010)
PURPOSE: To assess the relationships of microstructural damage in the cerebral white matter (WM), as measured by diffusion tensor imaging (DTI), with clinical parameters and magnetic resonance imaging (MRI) measures of focal tissue damage in patients with multiple sclerosis (MS). MATERIALS AND METHODS: Forty-five relapsing-remitting (RR) MS patients (12 male, 33 female; median age = 29 years, Expanded Disability Status Scale (EDSS) = 1.5, disease duration = 3 years) were studied. T2-lesion masks were created and voxelwise DTI analyses performed with Tract-Based Spatial Statistics (TBSS). RESULTS: T2-lesion volume (T2-LV) was significantly (P < 0.05, corrected) correlated with fractional anisotropy (FA) in both lesions and normal-appearing WM (NAWM). Relationships (P = 0.08, corrected) between increasing EDSS score and decreasing FA were found in the splenium of the corpus callosum (sCC) and along the pyramidal tract (PY). All FA associations were driven by changes in the perpendicular (to primary tract direction) diffusivity. No significant global and voxelwise FA changes were found over a 2-year follow-up. CONCLUSION: FA changes related to clinical disability in RR-MS patients with minor clinical disability are localized to specific WM tracts such as the sCC and PY and are driven by changes in perpendicular diffusivity both within lesions and NAWM. Longitudinal DTI measurements do not seem able to chart the early disease course in the WM of MS patients.